Legousia snogerupii (Campanulaceae), a new species from southeastern Kiklades, Greece - Tan, Kit; Biel, Burkhard; Sfikas, Giorgos (Phytotaxa, 2015)
Legousia snogerupii (Campanulaceae) from the islands of southeastern Kiklades, Greece is described as a species new to science and illustrated by photographs. It bears some morphological similarity to and had previously been confused with L. speculum-veneris which is absent from the area. Its affinities are, however, closer to L. pentagonia, rather common in the Kiklades. Morphological characteristics and information on ecology and distribution are provided and the three taxa compared.